Zirconium cesium tungsten oxide micron-sized powder, transparent coating for blocking infrared and ultraviolet rays, preparation method and coating thereof
By using zirconium cesium tungsten oxide micron-sized powder and hollow sphere composite oxide micron-sized powder, combined with processes such as ball milling dispersion and hydrothermal adsorption reaction, the problem of difficulty in dispersing the powder is solved, and high-efficiency blocking of infrared and ultraviolet rays is achieved. The preparation of clear coatings improves their performance and adhesion.
Patent Information
- Application Number
- CN202410894484.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2024-06-27
- Filing Date
- 2024-07-04
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-07-04
AI Technical Summary
During the preparation process, existing transparent coatings that block infrared and ultraviolet rays have problems such as difficult to disperse, easily agglomerate, and settle, which affects their performance.
The tungsten oxide micron meter and the hollow ball composite oxide micron meter are used. The combination of solid acrylic resin with specific hybrid pulp and water -based ultraviolet light, combined with the scattered ball mill and water thermal adsorption reactions to prepare to prepare it to prepare it Efficient blocking of transparent coatings of infrared and ultraviolet rays.
Achieve good dispersing powder, improve the blocking effect and adhesion of the coating, enhance its blocking performance of infrared and ultraviolet rays, and improve transparency and thermal insulation performance.
Smart Images

Figure CN118851795B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of transparent coatings for blocking infrared rays and ultraviolet rays, and in particular to a zirconium-cesium-tungsten oxide micron-sized powder, a transparent coating for blocking infrared rays and ultraviolet rays, and a preparation method and coating thereof. Background Art
[0002] Building energy conservation must first start with doors and windows, and high-performance selective shielding materials can make glass have selective transmittance to the spectrum. While being able to transmit most visible light without affecting lighting, the material can also block infrared and ultraviolet rays and block thermal radiation, thereby reducing the energy consumption of refrigeration or heating equipment and achieving the purpose of energy saving.
[0003] At present, some transparent coatings that can block infrared and ultraviolet rays have gradually appeared on the market. Patent CN102732108A discloses a new transparent coating made of a nanomaterial system, which has a good shielding effect on all near-infrared and ultraviolet rays of solar radiation. The coating has excellent water resistance, aging resistance and other properties, and has a self-cleaning function. However, the coating has the problems of a long and complicated preparation process, and the nano-oxide in the coating raw material is difficult to disperse in an aqueous solution, and is easy to agglomerate and settle.
[0004] Therefore, how to solve the problems of difficult dispersion, easy agglomeration and sedimentation of coatings is the current technical difficulty. Summary of the invention
[0005] The purpose of the present application is to provide a zirconium-cesium-tungsten oxide micron-sized powder, a transparent coating for blocking infrared and ultraviolet rays, and a preparation method and coating thereof, so as to solve the above-mentioned problems.
[0006] To achieve the above objectives, the present application provides a zirconium cesium tungsten oxide micron-sized powder, the molecular formula of which is Zr 0.04 CS 0.33 WO4.
[0007] The second aspect of the present application provides a method for preparing the zirconium-cesium-tungsten oxide micron-sized powder, comprising:
[0008] Mixing an aqueous zirconium oxychloride solution, an aqueous ammonium tungstate solution, and an aqueous cesium carbonate solution to obtain a first mixed solution;
[0009] Performing a first drying on the first mixed solution to obtain a mixed powder;
[0010] Under a hydrogen atmosphere, reducing and roasting the mixed powder to obtain a reducing and roasting product;
[0011] The reduction calcination product is calcined at high temperature under an inert atmosphere to obtain the zirconium-cesium-tungsten oxide micron-sized powder.
[0012] Optionally, the method for preparing the zirconium-cesium-tungsten oxide micron-sized powder satisfies at least one of the following conditions:
[0013] A. the concentration of the zirconium oxychloride aqueous solution in the first mixed solution is 0.005 mol / L-0.1 mol / L;
[0014] B. The concentration of the ammonium tungstate aqueous solution in the first mixed solution is 0.05 mol / L-2 mol / L;
[0015] C. the concentration of the cesium carbonate aqueous solution in the first mixed solution is 0.05 mol / L-0.2 mol / L;
[0016] D. The first drying temperature is 110°C-220°C and the time is 1h-48h;
[0017] E. The reduction roasting atmosphere further includes nitrogen, and the flow ratio of the hydrogen to the nitrogen is (1-9): 1;
[0018] F. The high temperature calcination temperature is 600°C-800°C and the time is 1h-8h.
[0019] The third aspect of the present application provides a transparent coating for blocking infrared rays and ultraviolet rays, wherein the raw materials thereof, calculated by mass fraction of 100%, include:
[0020] Mixing 0.2wt%-40wt% of slurry and 60.0wt%-99.8wt% of water-based UV-curable acrylic resin;
[0021] The raw materials of the mixed slurry include the zirconium cesium tungsten oxide micron-sized powder, the first dispersant, ethanol and hollow sphere composite oxide micron-sized powder;
[0022] The raw materials of the mixed slurry are calculated based on a mass fraction of 100%, the zirconium cesium tungsten oxide micron-sized powder is 0.1wt%-20wt%, the first dispersant is 0.5wt%-5wt%, the ethanol is 55wt%-99.3wt%, and the hollow sphere composite oxide micron-sized powder is 0.1wt%-20wt%;
[0023] The hollow sphere composite oxide micron-sized powder comprises zinc titanate, zinc oxide and titanium dioxide.
[0024] The fourth aspect of the present application provides a method for preparing the transparent coating that blocks infrared and ultraviolet rays, comprising:
[0025] Mixing the zirconium-cesium-tungsten oxide micron-sized powder, the first dispersant, the ethanol and the hollow sphere composite oxide micron-sized powder to obtain a mixed slurry;
[0026] The mixed slurry and the water-based ultraviolet light-curing acrylic resin are mixed to obtain the transparent coating that blocks infrared rays and ultraviolet rays.
[0027] Optionally, the method for preparing the transparent coating for blocking infrared and ultraviolet rays satisfies at least one of the following conditions:
[0028] A. The preparation method of the hollow sphere composite oxide micron-sized powder comprises:
[0029] The adsorbent, urea, titanyl sulfate, zinc nitrate, water, a second dispersant and ethanol are mixed to obtain a second mixed solution, and the second mixed solution is subjected to a hydrothermal adsorption reaction to obtain a hydrated ceramic oxide;
[0030] performing a second drying on the hydrated ceramic oxide to obtain a ceramic oxide;
[0031] The ceramic oxide is subjected to a first calcination and a second calcination to obtain the hollow sphere composite oxide micron-sized powder composed of the zinc titanate, the zinc oxide and the titanium dioxide;
[0032] The adsorbent includes one or more of yellow bamboo powder, bagasse powder and peanut shell powder;
[0033] The second dispersant includes polyethylene glycol;
[0034] The mass ratio of the water, the second dispersant and the ethanol is (100 mL-500 mL): (0.5 mL-5 mL): (500 mL-900 mL);
[0035] The concentration of the adsorbent in the second mixed solution is 5 g / L-100 g / L;
[0036] The concentration of urea in the second mixed solution is 0.3 mol / L-6 mol / L;
[0037] The concentration of titanyl sulfate in the second mixed solution is 0.1 mol / L-1 mol / L;
[0038] The concentration of the zinc nitrate in the second mixed solution is 0.1 mol / L-2 mol / L; B. the first dispersant includes BYK2001.
[0039] Optionally, the method for preparing the transparent coating for blocking infrared and ultraviolet rays satisfies at least one of the following conditions:
[0040] A. The temperature of the hydrothermal adsorption reaction is 80°C-160°C and the time is 2h-8h;
[0041] B. The second drying temperature is 80°C-120°C and the time is 12h-48h;
[0042] C. The first calcination temperature is 400°C-550°C, and the time is 4h-8h;
[0043] D. The second calcination temperature is 600°C-800°C, and the time is 2h-4h;
[0044] E. The heating rates of the first calcination and the second calcination are 2°C / min-5°C / min.
[0045] Optionally, before the zirconium-cesium-tungsten oxide micron-sized powder and the hollow sphere composite oxide micron-sized powder are mixed, the process further comprises:
[0046] The zirconium-cesium-tungsten oxide micron-sized powder and the hollow sphere composite oxide micron-sized powder are respectively dispersed by ball milling in an alkaline solution and a second dispersant to obtain zirconium-cesium-tungsten oxide nano-sized powder and hollow sphere composite oxide nano-sized powder;
[0047] The zirconium-cesium-tungsten oxide nano-powder, the hollow sphere composite oxide nano-powder and other raw materials are mixed to prepare a mixed slurry.
[0048] Optionally, the method for preparing the transparent coating for blocking infrared and ultraviolet rays satisfies at least one of the following conditions:
[0049] A. The pH of the alkaline solution is 7-10;
[0050] B. The ball milling dispersion speed is 500rpm / min-3000rpm / min, and the time is 70h-74h.
[0051] The fifth aspect of the present application provides a coating, the raw materials of which include the transparent coating that blocks infrared rays and ultraviolet rays.
[0052] Compared with the prior art, the beneficial effects of this application include:
[0053] The zirconium-cesium-tungsten oxide micron-sized powder provided by the present application has zirconium element inserted into the interface between the cesium-tungsten compound particles, which limits the growth of the cesium tungsten particles and obtains a nearly spherical zirconium-cesium-tungsten oxide with a small and uniform particle size. The addition of zirconium element also increases the oxidation resistance and weather resistance of the cesium tungsten oxide, thereby improving its utilization rate.
[0054] The present application provides a method for preparing zirconium-cesium-tungsten oxide micron-sized powder. H2 is used as a reducing agent. During the H2 reduction and inert gas calcination process, zirconium oxychloride, ammonium tungstate and cesium carbonate form zirconium-cesium tungsten oxide micron-sized powder. The metal element zirconium can effectively increase the reaction rate and stabilize the reaction process. The preparation method has low energy consumption, high efficiency, simple operation and less pollution.
[0055] The transparent coating for blocking infrared and ultraviolet rays provided by the present application comprises raw materials including a mixed slurry and an aqueous ultraviolet-curing acrylic resin. The hollow sphere composite oxide in the mixed slurry mainly acts on the absorption of ultraviolet light and blocks part of the infrared light. The zirconium-cesium-tungsten oxide mainly acts on the absorption of near-infrared light and blocks part of the ultraviolet light. The mixed use of the two components greatly improves the blocking effect of near-infrared and ultraviolet rays. The dispersant prevents agglomeration. Ethanol is used as a solvent. The zirconium-cesium-tungsten oxide micron-sized powder and the hollow sphere composite oxide micron-sized powder can be better dissolved in ethanol. The aqueous ultraviolet-curing acrylic resin increases the adhesion of the mixed slurry, thereby increasing the peeling strength between the dried coating and the glass, better bonding the glass, and improving the hardness and glossiness of the transparent coating.
[0056] The present application provides a method for preparing a transparent coating that blocks infrared and ultraviolet rays. First, micron-sized powder, a first dispersant, ethanol and hollow sphere composite oxide micron-sized powder are mixed to obtain a mixed slurry. The first dispersant and ethanol allow the two powders to be fully mixed and reduce the viscosity of the system, thereby preventing the two powders from agglomerating to obtain a mixed slurry with low viscosity and good dispersibility. The mixed slurry is then mixed with an aqueous ultraviolet light-curing acrylic resin to obtain a transparent coating, thereby avoiding the problems of uneven system viscosity and uneven dispersion of the two powders, resulting in separation and agglomeration, when the aqueous ultraviolet light-curing acrylic resin is used simultaneously with the first dispersant and ethanol, and the adhesion of the entire coating system is reduced, resulting in reduced heat insulation, ultraviolet protection and transparency of the coating.
[0057] The coating provided in the present application has a visible light transmittance greater than 70%, a near infrared and ultraviolet transmittance less than 10%, and has the function of blocking infrared and ultraviolet rays. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0059] Figure 1 This is a scanning electron microscope image of the zirconium-cesium-tungsten oxide micron-sized powder prepared in Example 1;
[0060] Figure 2A schematic flow chart of the method for preparing the zirconium-cesium-tungsten oxide micron-sized powder provided in Example 1;
[0061] Figure 3 A schematic diagram of the process for preparing the hollow sphere composite oxide micron-sized powder provided in Example 1;
[0062] Figure 4 The schematic diagram of the preparation process of the nano-sized powder of zirconium-cesium-tungsten oxide and the nano-sized powder of hollow sphere composite oxide in Example 1;
[0063] Figure 5 A schematic flow chart of a method for preparing a transparent coating for blocking infrared and ultraviolet rays provided in Example 1;
[0064] Figure 6 This is a schematic diagram of the process for preparing the coating provided in Example 1. DETAILED DESCRIPTION
[0065] As used herein:
[0066] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0067] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0068] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0069] In these examples, parts and percentages are by mass unless otherwise indicated.
[0070] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0071] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0072] The first aspect of the present application provides a zirconium-cesium-tungsten oxide micron-sized powder, the molecular formula of which is Zr 0.04 CS 0.33 WO4.
[0073] It should be noted that cesium tungsten oxide is a type of semiconductor material with non-stoichiometric narrow bandgap width, but cesium tungsten oxide has low reaction efficiency, long reaction cycle, large and non-uniform particles. The addition of zirconium element can improve this problem. Zirconium oxychloride is not only resistant to high temperature, but also can be used as a catalyst and stabilizer to improve and stabilize the micron-level powder molding of zirconium cesium tungsten oxide during high-temperature reduction reaction.
[0074] The second aspect of the present application provides a method for preparing the zirconium-cesium-tungsten oxide micron-sized powder, comprising:
[0075] Mixing an aqueous zirconium oxychloride solution, an aqueous ammonium tungstate solution, and an aqueous cesium carbonate solution to obtain a first mixed solution;
[0076] Performing a first drying on the first mixed solution to obtain a mixed powder;
[0077] Under a hydrogen atmosphere, reducing and roasting the mixed powder to obtain a reducing and roasting product;
[0078] The reduction calcination product is calcined at high temperature under an inert atmosphere to obtain the zirconium-cesium-tungsten oxide micron-sized powder.
[0079] In some embodiments, the method for preparing the zirconium-cesium-tungsten oxide micron-sized powder satisfies at least one of the following conditions:
[0080] A. the concentration of the zirconium oxychloride aqueous solution in the first mixed solution is 0.005 mol / L-0.1 mol / L;
[0081] Optionally, the concentration of the zirconium oxychloride aqueous solution in the first mixed solution may be 0.005 mol / L, 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L or any value between 0.005 mol / L and 0.1 mol / L;
[0082] B. The concentration of the ammonium tungstate aqueous solution in the first mixed solution is 0.05 mol / L-2 mol / L;
[0083] Optionally, the concentration of the ammonium tungstate aqueous solution in the first mixed solution may be 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 1 mol / L, 2 mol / L or any value between 0.05 mol / L and 2 mol / L;
[0084] C. the concentration of the cesium carbonate aqueous solution in the first mixed solution is 0.05 mol / L-0.2 mol / L;
[0085] Optionally, the concentration of the cesium carbonate aqueous solution in the first mixed solution may be 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 0.2 mol / L or any value between 0.05 mol / L and 0.2 mol / L;
[0086] D. The first drying temperature is 110°C-220°C and the time is 1h-48h;
[0087] Optionally, the temperature of the first drying can be 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C or any value between 110°C and 220°C, and the time can be 1h, 5h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 48h or any value between 1h and 48h;
[0088] E. The reduction roasting atmosphere further includes nitrogen, and the flow ratio of the hydrogen to the nitrogen is (1-9): 1;
[0089] Optionally, the flow ratio of hydrogen to nitrogen in the reduction roasting can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or any value between (1-9):1;
[0090] It should be noted that when the flow ratio of hydrogen and nitrogen in the reduction roasting is (1-9):1, N2 is added to prevent O2 from participating in the destruction of substances, and the increase in the proportion of H2 can fully carry out the reduction reaction.
[0091] F. The high temperature calcination temperature is 600°C-800°C and the time is 1h-8h.
[0092] Optionally, the temperature of high temperature calcination can be 600℃, 650℃, 700℃, 750℃, 800℃ or any value between 600℃-800℃, and the time can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h or any value between 1h-8h.
[0093] It should be understood that reduction roasting is performed first and then high-temperature roasting. During the reduction roasting process, ammonium tungstate is first converted into tungsten trioxide, and then the tungsten trioxide is reduced with high-temperature H2 to obtain submicron tungsten powder, which is then roasted in a high-temperature inert atmosphere. Submicron tungsten powder, zirconium oxychloride and cesium carbonate react to generate zirconium-cesium tungsten oxide.
[0094] It should also be understood that the intermediate product submicron tungsten powder particles prepared by this method are spherical, and this morphology is conducive to the uniform shrinkage of the tungsten powder during the sintering process, and can achieve good size control.
[0095] It is worth noting that cesium tungsten oxide is not stable. A portion of the +6-valent tungsten atoms in the system will be reduced to +5-valent tungsten atoms, resulting in poor crystallinity of tungsten compounds, unstable materials, poor weather resistance, and other problems, and ultimately causing cesium tungsten oxide to lose its near-infrared light shielding performance. In the prior art, metal elements or metal salts are introduced as reducing agents to reduce tungsten-containing compounds to low-valent tungsten atoms, which are then oxidized to obtain small-sized high-valent tungsten compounds, which are mixed with cesium salts and calcined to obtain highly stable cesium tungsten powder. Although the above method slows down the oxidation of cesium tungsten to a certain extent, the preparation method is complicated and has problems such as washing, drying, and difficult waste liquid treatment. The present application uses H2 as a reducing agent, and can prepare stable cesium tungsten powder at a lower temperature and in a shorter time. The process is simple and efficient.
[0096] The third aspect of the present application provides a transparent coating for blocking infrared rays and ultraviolet rays, wherein the raw materials thereof, calculated by mass fraction of 100%, include:
[0097] Mixing 0.2wt%-40wt% of slurry and 60wt%-99.8wt% of water-based UV-curable acrylic resin;
[0098] Optionally, the raw materials of the transparent coating that blocks infrared and ultraviolet rays are calculated based on a mass fraction of 100%, and the mixed slurry can be 0.2wt%, 1wt%, 2wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or any value between 0.2wt% and 40wt%, and the water-based UV-curable acrylic resin can be 60wt%, 65wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 99.8wt% or any value between 60wt% and 99.8wt%;
[0099] The raw materials of the mixed slurry include the zirconium cesium tungsten oxide micron-sized powder, the first dispersant, ethanol and hollow sphere composite oxide micron-sized powder;
[0100] The raw materials of the mixed slurry are calculated based on a mass fraction of 100%, the zirconium cesium tungsten oxide micron-sized powder is 0.1wt%-20wt%, the first dispersant is 0.5wt%-5wt%, the ethanol is 55wt%-99.3wt%, and the hollow sphere composite oxide micron-sized powder is 0.1wt%-20wt%;
[0101] Optionally, the mixed slurry is calculated by mass fraction of 100%, the zirconium cesium tungsten oxide micron-sized powder can be 0.1wt%, 1wt%, 2wt%, 5wt%, 10wt%, 15wt%, 20wt% or any value between 0.1wt% and 20wt%, the first dispersant can be 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any value between 0.5wt% and 5wt%, ethanol can be 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 99.3wt% or any value between 55wt% and 99.3wt%, and the hollow sphere composite oxide micron-sized powder can be 0.1wt%, 1wt%, 2wt%, 5wt%, 10wt%, 15wt%, 20wt% or any value between 0.1wt% and 20wt%;
[0102] The hollow sphere composite oxide micron-sized powder comprises zinc titanate, zinc oxide and titanium dioxide.
[0103] It should be noted that the hollow sphere composite oxide composed of zinc titanate, zinc oxide and titanium dioxide can effectively block ultraviolet rays.
[0104] The fourth aspect of the present application provides a method for preparing the transparent coating that blocks infrared and ultraviolet rays, comprising:
[0105] Mixing the zirconium-cesium-tungsten oxide micron-sized powder, the first dispersant, the ethanol and the hollow sphere composite oxide micron-sized powder to obtain a mixed slurry;
[0106] The mixed slurry and the water-based ultraviolet light-curing acrylic resin are mixed to obtain the transparent coating that blocks infrared rays and ultraviolet rays.
[0107] In some embodiments, the method for preparing the transparent coating that blocks infrared and ultraviolet rays satisfies at least one of the following conditions:
[0108] A. The preparation method of the hollow sphere composite oxide micron-sized powder comprises:
[0109] The adsorbent, urea, titanyl sulfate, zinc nitrate, water, a second dispersant and ethanol are mixed to obtain a second mixed solution, and the second mixed solution is subjected to a hydrothermal adsorption reaction to obtain a hydrated ceramic oxide;
[0110] performing a second drying on the hydrated ceramic oxide to obtain a ceramic oxide;
[0111] The ceramic oxide is subjected to a first calcination and a second calcination to obtain the hollow sphere composite oxide micron-sized powder composed of the zinc titanate, the zinc oxide and the titanium dioxide;
[0112] It should be noted that zinc nitrate is subjected to a hydrothermal adsorption reaction to obtain zinc oxide, titanyl sulfate is subjected to a hydrothermal adsorption reaction to obtain titanium dioxide, and part of titanium dioxide, urea and part of zinc oxide are reacted to obtain zinc titanate, that is, the hydrated ceramic oxide is a composite of zinc oxide, titanium dioxide and zinc titanate, and then zinc oxide, titanium dioxide and zinc titanate are adsorbed onto the surface of the adsorbent respectively, a first calcination is performed to remove most of the adsorbent, and then a second calcination is performed to remove the residual adsorbent and stabilize the sedimentation while promoting crystal growth so that the hollow structure reaches the micron level with uniform size, and the prepared powder particles have no agglomeration and stabilize the sedimentation so that the filling property is good; after two calcinations, micron-level powders of zinc oxide hollow sphere composite oxide, micron-level powders of titanium dioxide hollow sphere composite oxide and micron-level powders of zinc titanate hollow sphere composite oxide are obtained, and the micron-level powders of hollow sphere composite oxide are composed of micron-level powders of zinc oxide, titanium dioxide and micron-level powders of zinc titanate hollow sphere composite oxide.
[0113] It should also be noted that titanyl sulfate is hydrolyzed to generate Ti(OH)4, and Ti(OH)4 undergoes hydrothermal reaction to obtain titanium dioxide; however, the hydrolysis of titanyl sulfate to generate Ti(OH)4 is a reversible reaction, and there is an equilibrium point. As the hydrothermal reaction proceeds, more and more Ti(OH)4 is generated, but more and more H + , causing the solution to become acidic, H +The increase of will promote the reaction to the reverse direction and inhibit the hydrolysis of titanyl sulfate. Therefore, urea is introduced into the reaction system. After adding urea, urea is decomposed into ammonia and carbon dioxide by heat. Ammonia dissolved in water can neutralize H in the solution. + , it can adjust the pH and promote the hydrolysis of titanyl sulfate. With the increase of hydrothermal reaction temperature and the extension of time, the decomposition rate of urea is accelerated and the decomposition amount increases, which is conducive to the formation of titanium dioxide.
[0114] It can be understood that zinc titanate is prepared by the reaction of zinc oxide and titanium dioxide, and the ultraviolet blocking performance of the three hollow sphere composite oxide micron powders is best when used simultaneously, which is stronger than the ultraviolet blocking performance of using one or two of the hollow sphere composite oxide micron powders.
[0115] The adsorbent includes one or more of yellow bamboo powder, bagasse powder and peanut shell powder;
[0116] It should be noted that when the adsorbent includes one or more of yellow bamboo powder, bagasse powder and peanut shell powder, the adsorbent is used as the core, and the adsorbent adsorbs zinc oxide, titanium dioxide and zinc titanate on its own surface to form a protective shell, which is washed, separated, dried and roasted with water and ethanol; the adsorbent decomposes and disappears at high temperature, and the shell formed by zinc oxide, titanium dioxide and zinc titanate does not decompose, thereby forming a hollow shell and a hollow ceramic oxide; the hollow ceramic oxide structure has many excellent properties such as superior optical properties, spherical lens characteristics, strong impact resistance, good rolling properties, low thermal conductivity, thermal insulation, and high electrical insulation strength.
[0117] The second dispersant includes polyethylene glycol;
[0118] It should be noted that the dispersant can first increase the solubility of urea, titanyl sulfate and zinc nitrate in water; secondly, it can also improve the stability of titanyl sulfate that is easily decomposed in water, prevent all titanyl sulfate from being hydrolyzed into titanium dioxide, and allow a part of the titanyl sulfate to undergo hydrothermal reaction to obtain titanium dioxide; and polyethylene glycol is non-toxic and non-irritating, and will not remain, deposit or generate volatiles during the product production process, and finally increase the surface activity of the solution to prevent zinc oxide, titanium dioxide and zinc titanate from agglomerating.
[0119] The mass ratio of the water, the second dispersant and the ethanol is (100 mL-500 mL): (0.5 mL-5 mL): (500 mL-900 mL);
[0120] Optionally, the mass ratio of water can be 100mL, 200mL, 300mL, 400mL, 500mL or any value between 100mL-500mL, the mass ratio of the second dispersant can be 0.5mL, 1mL, 2mL, 3mL, 4mL, 5mL or any value between 0.5mL-5mL, and the mass ratio of ethanol can be 500mL, 600mL, 700mL, 800mL, 900mL or any value between 500mL-900mL;
[0121] The concentration of the adsorbent in the second mixed solution is 5 g / L-100 g / L;
[0122] Optionally, the concentration of the adsorbent in the second mixed solution may be 5 g / L, 10 g / L, 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L or any value between 5 g / L and 100 g / L; the concentration of urea in the second mixed solution is 0.3 mol / L-6 mol / L;
[0123] Optionally, the concentration of urea in the second mixed solution may be 0.3 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L or any value between 0.3 mol / L and 6 mol / L;
[0124] The concentration of titanyl sulfate in the second mixed solution is 0.1 mol / L-1 mol / L;
[0125] Optionally, the concentration of titanyl sulfate in the second mixed solution may be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L or any value between 0.1 mol / L and 1 mol / L;
[0126] The concentration of zinc nitrate in the second mixed solution is 0.1 mol / L-2 mol / L;
[0127] Optionally, the concentration of zinc nitrate in the second mixed solution may be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 2 mol / L or any value between 0.1 mol / L and 2 mol / L;
[0128] B. The first dispersant includes BYK2001.
[0129] It should be noted that BYK2001 dispersant deflocculates the coating through steric stabilization, and also makes the coating particles carry the same charge, thereby producing a repulsive effect and steric stabilization to prevent the aggregation of hollow sphere composite oxide micron powder and zirconium cesium tungsten oxide micron powder, and finally eliminate the problem of floating color and blooming; and because the particle size of the two micron powder coatings is small, BYK2001 can also improve the gloss and enhance the color strength, so that the hiding power of the coating can also be improved; BYK2001 can also reduce the viscosity of the grinding material. Due to the reduction in viscosity, the leveling performance of the coating is improved.
[0130] It should also be noted that the addition of BYK-2001 may cause a temporary increase in the viscosity of the mixed coating system. This is because BYK-2001 imparts charge properties to the coating particles, but has no effect on the final dispersion result. Ethanol is added to neutralize the charge and prevent the viscosity of the entire coating system from increasing. The ethanol in this application is both a solvent and an additive.
[0131] In some embodiments, the method for preparing the transparent coating that blocks infrared and ultraviolet rays satisfies at least one of the following conditions:
[0132] A. The temperature of the hydrothermal adsorption reaction is 80°C-160°C and the time is 2h-8h;
[0133] Optionally, the temperature of the hydrothermal adsorption reaction can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C or any value between 80°C and 160°C, and the time can be 2h, 3h, 4h, 5h, 6h, 7h, 8h or any value between 2h and 8h;
[0134] It should be noted that, based on the property that zinc nitrate and titanyl sulfate are easily soluble in water, the present application adopts a hydrothermal method to obtain zinc oxide and titanium dioxide in water, and then prepares zinc titanate. The hydrothermal method for preparing ceramic powder does not require high-temperature calcination treatment, thus avoiding grain growth, defect formation and impurity introduction caused by the calcination process. The method is simple, and the prepared powder has complete grain development, small particle size, uniform distribution, and less particle agglomeration.
[0135] B. The second drying temperature is 80°C-120°C and the time is 12h-48h;
[0136] Optionally, the second drying temperature may be 80°C, 90°C, 100°C, 110°C, 120°C or any value between 80°C and 120°C, and the time may be 12h, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 48h or any value between 12h and 48h;
[0137] C. The first calcination temperature is 400°C-550°C, and the time is 4h-8h;
[0138] Optionally, the temperature of the first calcination may be 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C or any value between 400°C and 550°C, and the time may be 4h, 5h, 6h, 7h, 8h or any value between 4h and 8h;
[0139] D. The second calcination temperature is 600°C-800°C, and the time is 2h-4h;
[0140] Optionally, the temperature of the second calcination may be 600°C, 650°C, 700°C, 750°C, 800°C or any value between 600°C and 800°C, and the time may be 2h, 3h, 4h or any value between 2h and 4h;
[0141] It should be noted that the second-stage roasting can fully decompose the adsorbent, improve the yield of the hollow structure, and increase the volume density of the finished product;
[0142] E. The heating rates of the first calcination and the second calcination are 2°C / min-5°C / min.
[0143] Optionally, the heating rates of the first calcination and the second calcination may be 2° C. / min, 3° C. / min, 4° C. / min, 5° C. / min or any value between 2° C. / min and 5° C. / min.
[0144] In some embodiments, before the zirconium-cesium-tungsten oxide micron-sized powder and the hollow sphere composite oxide micron-sized powder are mixed, the process further includes:
[0145] The zirconium-cesium-tungsten oxide micron-sized powder and the hollow sphere composite oxide micron-sized powder are respectively dispersed by ball milling in an alkaline solution and a second dispersant to obtain zirconium-cesium-tungsten oxide nano-sized powder and hollow sphere composite oxide nano-sized powder;
[0146] The zirconium-cesium-tungsten oxide nano-powder, the hollow sphere composite oxide nano-powder and other raw materials are mixed to prepare a mixed slurry.
[0147] It should be noted that ball milling and dispersion of micron-scale powders into nano-scale powders can greatly enhance the performance of the material itself, improve the material's ability to block infrared and ultraviolet rays, and because the particle size is nanometer-scale, it can increase the heat conduction path and further improve the thermal insulation effect of the material.
[0148] In some embodiments, the method for preparing the transparent coating that blocks infrared and ultraviolet rays satisfies at least one of the following conditions:
[0149] A. The pH of the alkaline solution is 7-10;
[0150] Optionally, the pH of the alkaline solution may be 7, 8, 9, 10 or any value between 7 and 10;
[0151] It should be noted that the dispersant PEG6000 is stable under alkaline conditions, and the micronized powder will not agglomerate under alkaline conditions and will be evenly dispersed.
[0152] B. The ball milling dispersion speed is 500rpm / min-3000rpm / min, and the time is 70h-74h.
[0153] Optionally, the ball milling dispersion speed can be 500rpm / min, 1000rpm / min, 1500rpm / min, 2000rpm / min, 2500rpm / min, 3000rpm / min or any value between 500rpm / min-3000rpm / min, and the time can be 70h, 71h, 72h, 73h, 74h or any value between 70h-74h.
[0154] The fifth aspect of the present application provides a coating, the raw materials of which include the transparent coating that blocks infrared rays and ultraviolet rays.
[0155] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0156] Example 1
[0157] The first aspect of the present embodiment provides a zirconium cesium tungsten oxide micron-sized powder and a preparation method thereof, comprising:
[0158] A zirconium oxychloride aqueous solution, an ammonium tungstate aqueous solution and a cesium carbonate aqueous solution are mixed, and magnetic stirring and ultrasonic dispersion are performed to obtain a mixed solution, wherein the concentration of the zirconium oxychloride aqueous solution in the mixed solution is 0.005 mol / L, the concentration of the ammonium tungstate aqueous solution is 0.05 mol / L, and the concentration of the cesium carbonate aqueous solution is 0.05 mol / L;
[0159] The mixed solution was dried at 110°C for 10 h to obtain a mixed powder;
[0160] The mixed powder was reduction-calcined at 400°C for 2h to obtain a reduction-calcined product, wherein the flow ratio of H2 and N2 introduced during the reduction-calcination process was 1:1;
[0161] The reduced calcined product was calcined at 600°C for 2 h in an argon atmosphere to obtain micron-sized zirconium-cesium-tungsten oxide powder, namely Zr 0.04 CS 0.33 WO4 micron powder, the Zr 0.04 CS 0.33 WO4 micron powder is nearly spherical, Zr 0.04 CS 0.33 The scanning electron microscope image of WO4 micron powder is as follows: Figure 1 As shown;
[0162] The preparation method of zirconium cesium tungsten oxide micron powder is as follows: Figure 2 As shown;
[0163] The second aspect of the present embodiment provides a transparent coating for blocking infrared and ultraviolet rays and a preparation method thereof. The raw materials of the transparent coating for blocking infrared and ultraviolet rays include: 0.2wt% of mixed slurry and 99.8wt% of water-based ultraviolet light-cured acrylic resin, calculated by mass fraction of 100%;
[0164] The raw materials of the mixed slurry are calculated based on a mass fraction of 100%, the zirconium cesium tungsten oxide micron-sized powder is 10wt%, the first dispersant BYK2001 is 0.5wt%, ethanol is 79.5wt%, and the hollow sphere composite oxide micron-sized powder is 10wt%;
[0165] The hollow sphere composite oxide micron-sized powder comprises zinc titanate, zinc oxide and titanium dioxide.
[0166] The preparation method of hollow spherical composite oxide micron-sized powder comprises: mixing adsorbent yellow bamboo powder, urea, titanyl sulfate, zinc nitrate, water, a second dispersant polyethylene glycol 300 and ethanol to obtain a mixed solution, wherein the mass ratio of water, the second dispersant and ethanol is 100 mL: 0.5 mL: 500 mL, the concentration of the adsorbent in the mixed solution is 5 g / L, the concentration of urea is 0.3 mol / L, the concentration of titanyl sulfate is 0.1 mol / L, and the concentration of zinc nitrate is 0.1 mol / L; performing annealing at 80°C The hydrated ceramic oxide is obtained by a hydrothermal adsorption reaction for 2 hours, and the hydrated ceramic oxide is dried by hot air at 80°C for 12 hours to obtain a ceramic oxide, and then heated in air for a first calcination, the temperature of the first calcination is 400°C, and the time is 4 hours. After the first calcination, a second calcination is continued, the temperature of the second calcination is 600°C, and the time is 2 hours. The heating rate of the first calcination and the second calcination is 2°C / min, and finally a hollow sphere composite oxide micron powder composed of three compounds of zinc titanate, zinc oxide and titanium dioxide is obtained;
[0167] The preparation method of hollow spherical composite oxide micron powder is as follows: Figure 3 As shown;
[0168] The preparation method of the transparent coating for blocking infrared and ultraviolet rays comprises:
[0169] The first step: the zirconium cesium tungsten oxide micron-sized powder and the hollow sphere composite oxide micron-sized powder are respectively dispersed by ball milling with the second dispersant PEG-6000 in an alkaline aqueous solution with a pH of 8.0, the dispersant PEG-6000 accounts for 0.5wt%, and grinding beads ZrO2 are added. The grinding beads account for 20wt% of the entire ball milling system. The ball milling dispersion speed is 500rpm / min, and the time is 70h, and the zirconium cesium tungsten oxide nano-sized powder and the hollow sphere composite oxide nano-sized powder are obtained respectively;
[0170] The preparation method of zirconium cesium tungsten oxide nanopowder and hollow sphere composite oxide nanopowder is as follows Figure 4 As shown;
[0171] Step 2: Mix the zirconium cesium tungsten oxide nanopowder, the hollow sphere composite oxide nanopowder first dispersant BYK2001 and ethanol in the above proportions, perform magnetic stirring and ball milling dispersion to prepare a mixed slurry, and mix the mixed slurry with a water-based UV-curable acrylic resin to obtain a transparent coating that blocks infrared and ultraviolet rays.
[0172] Preparation method of transparent coating for blocking infrared and ultraviolet rays Figure 5 As shown;
[0173] A third aspect of this embodiment provides a coating, the raw materials of which include the above-mentioned transparent coating that blocks infrared rays and ultraviolet rays.
[0174] The coating preparation method is as follows Figure 6 shown.
[0175] Example 2
[0176] The first aspect of the present embodiment provides a zirconium cesium tungsten oxide micron-sized powder and a preparation method thereof, comprising:
[0177] A zirconium oxychloride aqueous solution, an ammonium tungstate aqueous solution and a cesium carbonate aqueous solution are mixed, and magnetic stirring and ultrasonic dispersion are performed to obtain a mixed solution, wherein the concentration of the zirconium oxychloride aqueous solution in the mixed solution is 0.1 mol / L, the concentration of the ammonium tungstate aqueous solution is 2 mol / L, and the concentration of the cesium carbonate aqueous solution is 0.2 mol / L;
[0178] The mixed solution was dried at 220°C for 48 h to obtain a mixed powder;
[0179] The mixed powder was reduction-roasted at 650°C for 8 hours to obtain a reduction-roasted product, wherein the flow ratio of H2 and N2 introduced during the reduction-roasting process was 9:1;
[0180] The reduced calcined product was calcined at 800° C. for 8 h under an argon atmosphere to obtain zirconium-cesium-tungsten oxide micron-sized powder.
[0181] The second aspect of the present embodiment provides a transparent coating for blocking infrared and ultraviolet rays and a preparation method thereof. The raw materials of the transparent coating for blocking infrared and ultraviolet rays include 40 wt % of mixed slurry and 60.0 wt % of water-based ultraviolet light-curing acrylic resin, calculated by mass fraction of 100 wt %;
[0182] The raw materials of the mixed slurry are calculated based on a mass fraction of 100%, the zirconium cesium tungsten oxide micron-sized powder is 20wt%, the first dispersant BYK2001 is 5wt%, ethanol is 55wt%, and the hollow sphere composite oxide micron-sized powder is 20wt%;
[0183] The hollow sphere composite oxide micron-sized powder comprises zinc titanate, zinc oxide and titanium dioxide.
[0184] The preparation method of hollow spherical composite oxide micron-sized powder comprises: mixing adsorbent bagasse powder, urea, titanyl sulfate, zinc nitrate, water, a second dispersant polyethylene glycol 300 and ethanol to obtain a mixed solution, wherein the mass ratio of water, the second dispersant and ethanol is 500 mL: 5 mL: 900 mL, the concentration of the adsorbent in the mixed solution is 50 g / L, the concentration of urea is 6 mol / L, the concentration of titanyl sulfate is 1 mol / L, and the concentration of zinc nitrate is 2 mol / L; performing hydrothermal absorption at 160°C; The hydrated ceramic oxide is obtained by reacting for 8 hours, and the hydrated ceramic oxide is dried by hot air at 120°C for 48 hours to obtain a ceramic oxide, and then heated in air for a first calcination, the temperature of the first calcination is 550°C, and the time is 8 hours. After the first calcination, a second calcination is performed, the temperature of the second calcination is 800°C, and the time is 4 hours. The heating rate of the first calcination and the second calcination is 5°C / min, and finally a hollow sphere composite oxide micron powder composed of three compounds of zinc titanate, zinc oxide and titanium dioxide is obtained;
[0185] The preparation method of the transparent coating for blocking infrared and ultraviolet rays comprises:
[0186] The first step: the zirconium cesium tungsten oxide micron-sized powder and the hollow sphere composite oxide micron-sized powder are respectively dispersed by ball milling with the second dispersant PEG-6000 in an alkaline aqueous solution with a pH of 10.0, the dispersant PEG-6000 accounts for 10wt%, and grinding beads ZrO2 are added. The grinding beads account for 60wt% of the entire ball milling system. The ball milling dispersion speed is 3000rpm / min, and the time is 74h, and the zirconium cesium tungsten oxide nano-sized powder and the hollow sphere composite oxide nano-sized powder are obtained respectively;
[0187] Step 2: Mix the zirconium cesium tungsten oxide nanopowder, the hollow sphere composite oxide nanopowder first dispersant BYK2001 and ethanol in the above proportions, perform magnetic stirring and ball milling dispersion to prepare a mixed slurry, and mix the mixed slurry with a water-based UV-curable acrylic resin to obtain a transparent coating that blocks infrared and ultraviolet rays.
[0188] A third aspect of this embodiment provides a coating, the raw materials of which include the above-mentioned transparent coating that blocks infrared rays and ultraviolet rays.
[0189] Example 3
[0190] The first aspect of the present embodiment provides a zirconium cesium tungsten oxide micron-sized powder and a preparation method thereof, comprising:
[0191] The zirconium oxychloride aqueous solution, the ammonium tungstate aqueous solution and the cesium carbonate aqueous solution are mixed, and magnetic stirring and ultrasonic dispersion are performed to obtain a mixed solution, wherein the concentration of the zirconium oxychloride aqueous solution in the mixed solution is 0.008 mol / L, the concentration of the ammonium tungstate aqueous solution is 1 mol / L, and the concentration of the cesium carbonate aqueous solution is 0.1 mol / L;
[0192] The mixed solution was dried at 200°C for 40 h to obtain a mixed powder;
[0193] The mixed powder was reduction-roasted at 600°C for 6 hours to obtain a reduction-roasted product, wherein the flow ratio of H2 and N2 introduced during the reduction-roasting process was 5:1;
[0194] The reduced calcined product was calcined at 800° C. for 4 h under an argon atmosphere to obtain zirconium-cesium-tungsten oxide micron-sized powder.
[0195] The second aspect of the present embodiment provides a transparent coating for blocking infrared and ultraviolet rays and a preparation method thereof. The raw materials of the transparent coating for blocking infrared and ultraviolet rays include: 20wt% of mixed slurry and 80wt% of water-based ultraviolet light-cured acrylic resin, calculated by mass fraction of 100%;
[0196] The raw materials of the mixed slurry are calculated based on a mass fraction of 100%, the zirconium cesium tungsten oxide micron-sized powder is 15wt%, the first dispersant BYK2001 is 5wt%, ethanol is 65wt%, and the hollow sphere composite oxide micron-sized powder is 15wt%;
[0197] The hollow sphere composite oxide micron-sized powder comprises zinc titanate, zinc oxide and titanium dioxide.
[0198] The preparation method of hollow spherical composite oxide micron-sized powder comprises: mixing adsorbent peanut shell powder, urea, titanyl sulfate, zinc nitrate, water, a second dispersant polyethylene glycol 300 and ethanol to obtain a mixed solution, wherein the mass ratio of water, the second dispersant and ethanol is 400 mL: 5 mL: 600 mL, the concentration of the adsorbent in the mixed solution is 60 g / L, the concentration of urea is 2 mol / L, the concentration of titanyl sulfate is 0.5 mol / L, and the concentration of zinc nitrate is 1 mol / L; performing hydrothermal treatment at 100°C; The adsorption reaction was performed for 4 hours to obtain a hydrated ceramic oxide, and the hydrated ceramic oxide was hot-air dried at 100°C for 40 hours to obtain a ceramic oxide, and then heated in air for a first calcination at a temperature of 500°C for 6 hours. After the first calcination, a second calcination was performed at a temperature of 700°C for 2 hours. The heating rate of the first calcination and the second calcination was 4°C / min, and finally a hollow sphere composite oxide micron powder composed of three compounds, namely zinc titanate, zinc oxide and titanium dioxide, was obtained.
[0199] The preparation method of the transparent coating for blocking infrared and ultraviolet rays comprises:
[0200] The first step: the zirconium cesium tungsten oxide micron-sized powder and the hollow sphere composite oxide micron-sized powder are respectively dispersed by ball milling with the second dispersant PEG-6000 in an alkaline aqueous solution with a pH of 9, the dispersant PEG-6000 accounts for 5wt%, and grinding beads ZrO2 are added. The grinding beads account for 40wt% of the entire ball milling system. The ball milling dispersion speed is 2000rpm / min, and the time is 72h, and the zirconium cesium tungsten oxide nano-sized powder and the hollow sphere composite oxide nano-sized powder are obtained respectively;
[0201] Step 2: Mix the zirconium cesium tungsten oxide nanopowder, the hollow sphere composite oxide nanopowder first dispersant BYK2001 and ethanol in the above proportions, perform magnetic stirring and ball milling dispersion to prepare a mixed slurry, and mix the mixed slurry with a water-based UV-curable acrylic resin to obtain a transparent coating that blocks infrared and ultraviolet rays.
[0202] A third aspect of this embodiment provides a coating, the raw materials of which include the above-mentioned transparent coating that blocks infrared rays and ultraviolet rays.
[0203] Comparative Example 1
[0204] This comparative example provides a micron-sized powder, a transparent coating that blocks infrared and ultraviolet rays, and a preparation method and coating thereof. The difference from Example 1 is that during the preparation of the zirconium cesium tungsten oxide micron-sized powder and the preparation method thereof in this comparative example, no zirconium oxychloride aqueous solution is added, and other conditions are consistent with Example 1.
[0205] Comparative Example 2
[0206] This comparative example provides a micron-sized powder, a transparent coating that blocks infrared and ultraviolet rays, and a preparation method and coating thereof. The difference from Example 1 is that during the preparation of the zirconium cesium tungsten oxide micron-sized powder and the preparation method thereof in this comparative example, no ammonium tungstate aqueous solution is added, and other conditions are consistent with those in Example 1.
[0207] Comparative Example 3
[0208] This comparative example provides a micron-sized powder, a transparent coating that blocks infrared and ultraviolet rays, and a preparation method and coating thereof. The difference from Example 1 is that during the preparation of the zirconium cesium tungsten oxide micron-sized powder and the preparation method thereof in this comparative example, no cesium carbonate aqueous solution is added, and other conditions are consistent with those in Example 1.
[0209] Comparative Example 4
[0210] This comparative example provides a micron-sized powder, a transparent coating that blocks infrared and ultraviolet rays, and a preparation method and coating thereof. The difference from Example 1 is that in the micron-sized zirconium-cesium-tungsten oxide powder and the preparation method thereof in this comparative example, the mixed powder is directly calcined at 600°C for 1 hour without reduction calcination, and the other conditions are the same as those in Example 1.
[0211] Comparative Example 5
[0212] This comparative example provides a micron-sized powder, a transparent coating that blocks infrared and ultraviolet rays, and a preparation method and coating thereof. The difference from Example 1 is that no adsorbent is added during the hollow sphere composite oxide micron-sized powder and the preparation method thereof in this comparative example, and other conditions are consistent with Example 1.
[0213] Comparative Example 6
[0214] This comparative example provides a micron-sized powder, a transparent coating that blocks infrared and ultraviolet rays, and a preparation method and coating thereof. The difference from Example 1 is that in the hollow sphere composite oxide micron-sized powder and the preparation method thereof in this comparative example, titanium oxysulfate is not added, and other conditions are consistent with Example 1.
[0215] Comparative Example 7
[0216] This comparative example provides a micron-sized powder, a transparent coating that blocks infrared and ultraviolet rays, and a preparation method and coating thereof. The difference from Example 1 is that in the hollow sphere composite oxide micron-sized powder and the preparation method thereof in this comparative example, no two-stage calcination is performed, the calcination temperature is 800°C, the time is 2h, and the other conditions are consistent with Example 1.
[0217] Comparative Example 8
[0218] This comparative example provides a micron-sized powder, a transparent coating that blocks infrared and ultraviolet rays, and a preparation method and coating thereof. The difference from Example 1 is that in the process of the transparent coating that blocks infrared and ultraviolet rays and the preparation method thereof in this comparative example, no zirconium cesium tungsten oxide nanopowder is added, and other conditions are consistent with Example 1.
[0219] Comparative Example 9
[0220] This comparative example provides a micron-sized powder, a transparent coating that blocks infrared and ultraviolet rays, and a preparation method and coating thereof. The difference from Example 1 is that in the process of the transparent coating that blocks infrared and ultraviolet rays and the preparation method thereof in this comparative example, no hollow sphere composite oxide nano-sized powder is added, and other conditions are consistent with Example 1.
[0221] Comparative Example 10
[0222] This comparative example provides a micron-sized powder, a transparent coating that blocks infrared and ultraviolet rays, a preparation method thereof, and a coating. The difference from Example 1 is that in the process of the transparent coating that blocks infrared and ultraviolet rays and the preparation method thereof in this comparative example, the first dispersant BYK2001 is not added, and other conditions are consistent with Example 1.
[0223] The coatings prepared in the above examples and comparative examples were tested for their infrared and ultraviolet blocking performance and heat insulation properties. The test results are shown in Table 1.
[0224] The specific test method is as follows: Infrared test method: Use near-infrared light with a wavelength of 940nm to irradiate the coated glass, and monitor the transmittance of infrared light on the back of the glass.
[0225] UV test method: Use UV light with a wavelength of 365nm to irradiate the coated glass, and monitor the transmittance of UV light on the back of the glass.
[0226] Visible light test method: Use near-infrared light with a wavelength of 530nm to irradiate the coated glass, and monitor the transmittance of visible light on the back of the glass.
[0227] Table 1 Infrared, ultraviolet blocking performance and visible light test
[0228]
[0229] It can be seen from Comparative Example 1 that when zirconium oxychloride is not added, under hydrogen reduction, cesium tungsten oxide has problems such as low reaction efficiency, large and non-uniform particles; the light transmittance increases, and the anti-ultraviolet performance decreases.
[0230] It can be seen from Comparative Example 2 that when ammonium tungstate is not added, cesium tungsten oxide cannot be generated, resulting in the inability to effectively block ultraviolet rays.
[0231] It can be seen from Comparative Example 3 that when cesium carbonate is not added, cesium tungsten oxide cannot be generated, resulting in the inability to effectively block ultraviolet rays.
[0232] It can be seen from Comparative Example 4 that without reduction roasting, only tungsten trioxide is generated, submicron spherical tungsten powder cannot be generated, and the ultraviolet transmittance is unqualified.
[0233] It can be seen from Comparative Example 5 that without adding an adsorbent, a hollow structure cannot be generated and the infrared blocking rate decreases.
[0234] It can be seen from Comparative Example 6 that without adding titanyl sulfate, titanium dioxide cannot be produced, and without titanium dioxide, zinc titanate cannot be generated, and the infrared blocking rate decreases.
[0235] It can be seen from Comparative Example 7 that without two-stage calcination, the adsorbent cannot be fully removed, the proportion of hollow ceramic microspheres is reduced, the transparency of the coating is reduced, and the transmittance of visible light is reduced.
[0236] It can be seen from Comparative Example 8 that without adding zirconium cesium tungsten oxide nanopowder, ultraviolet rays cannot be effectively blocked.
[0237] It can be seen from Comparative Example 9 that without adding the hollow sphere composite oxide nano-powder, infrared rays cannot be effectively blocked.
[0238] As can be seen from Comparative Example 10, dispersant BYK2001, as a wetting dispersant, can not only make the substances in the coating disperse evenly, but also reduce the viscosity of the grinding material. In magnetic stirring and ball milling dispersion, it is used as an auxiliary additive to further improve the dispersion of the two substances and prevent agglomeration. Without the addition of BYK2001, the two substances are unevenly dispersed and easily agglomerated, resulting in a decrease in infrared, ultraviolet and light transmittance.
[0239] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0240] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A zirconium-cesium-tungsten oxide micron-sized powder, characterized in that: Its molecular formula is Zr 0.04 CS 0.33 WO4; The method for preparing the zirconium-cesium-tungsten oxide micron-sized powder comprises: Mixing an aqueous zirconium oxychloride solution, an aqueous ammonium tungstate solution, and an aqueous cesium carbonate solution to obtain a first mixed solution; Performing a first drying on the first mixed solution to obtain a mixed powder; Under a hydrogen atmosphere, reducing and roasting the mixed powder to obtain a reducing and roasting product; The reduction calcination product is calcined at high temperature under an inert atmosphere to obtain the zirconium-cesium-tungsten oxide micron-sized powder.
2. The zirconium-cesium-tungsten oxide micron-sized powder according to claim 1, characterized in that: At least one of the following conditions is met: A. the concentration of the zirconium oxychloride aqueous solution in the first mixed solution is 0.005 mol / L-0.1 mol / L; B. The concentration of the ammonium tungstate aqueous solution in the first mixed solution is 0.05 mol / L-2 mol / L; C. the concentration of the cesium carbonate aqueous solution in the first mixed solution is 0.05 mol / L-0.2 mol / L; D. The first drying temperature is 110°C-220°C and the time is 1h-48h; E. The reduction roasting atmosphere further includes nitrogen, and the flow ratio of the hydrogen to the nitrogen is (1-9): 1; F. The high temperature calcination temperature is 600°C-800°C and the time is 1h-8h.
3. A transparent coating material for blocking infrared rays and ultraviolet rays, characterized in that: The raw materials, calculated by mass fraction as 100%, include: Mix slurry 0.2wt%-40wt% and water-based UV-curable acrylic resin 60.0wt%-99.8wt%; The raw materials of the mixed slurry include the zirconium-cesium-tungsten oxide micron-sized powder according to claim 1 or 2, a first dispersant, ethanol and hollow sphere composite oxide micron-sized powder; The raw materials of the mixed slurry are calculated based on a mass fraction of 100%, the zirconium cesium tungsten oxide micron-sized powder is 0.1wt%-20wt%, the first dispersant is 0.5wt%-5wt%, the ethanol is 55wt%-99.3wt%, and the hollow sphere composite oxide micron-sized powder is 0.1wt%-20wt%; The hollow sphere composite oxide micron-sized powder comprises zinc titanate, zinc oxide and titanium dioxide.
4. A method for preparing the transparent coating material for blocking infrared and ultraviolet rays according to claim 3, characterized in that: include: Mixing the above-mentioned micron-sized powder of zirconium-cesium-tungsten oxide, the first dispersant, the ethanol and the micron-sized powder of hollow sphere composite oxide to obtain a mixed slurry; The mixed slurry and the water-based ultraviolet light-curing acrylic resin are mixed to obtain the transparent coating that blocks infrared rays and ultraviolet rays.
5. The method for preparing the transparent coating material for blocking infrared rays and ultraviolet rays according to claim 4, characterized in that: At least one of the following conditions is met: A. The preparation method of the hollow sphere composite oxide micron-sized powder comprises: The adsorbent, urea, titanyl sulfate, zinc nitrate, water, a second dispersant and ethanol are mixed to obtain a second mixed solution, and the second mixed solution is subjected to a hydrothermal adsorption reaction to obtain a hydrated ceramic oxide; performing a second drying on the hydrated ceramic oxide to obtain a ceramic oxide; The ceramic oxide is subjected to a first calcination and a second calcination to obtain the hollow sphere composite oxide micron-sized powder composed of the zinc titanate, the zinc oxide and the titanium dioxide; The adsorbent includes one or more of yellow bamboo powder, bagasse powder and peanut shell powder; The second dispersant includes polyethylene glycol; The mass ratio of the water, the second dispersant and the ethanol is (100 mL-500 mL): (0.5 mL-5 mL): (500 mL-900 mL); The concentration of the adsorbent in the second mixed solution is 5 g / L-100 g / L; The concentration of urea in the second mixed solution is 0.3 mol / L-6 mol / L; The concentration of titanyl sulfate in the second mixed solution is 0.1 mol / L-1 mol / L; The concentration of zinc nitrate in the second mixed solution is 0.1 mol / L-2 mol / L; B. The first dispersant includes BYK2001.
6. The method for preparing the transparent coating material for blocking infrared rays and ultraviolet rays according to claim 5, characterized in that: At least one of the following conditions is met: A. The temperature of the hydrothermal adsorption reaction is 80°C-160°C and the time is 2h-8h; B. The second drying temperature is 80°C-120°C and the time is 12h-48h; C. The first calcination temperature is 400°C-550°C, and the time is 4h-8h; D. The second calcination temperature is 600°C-800°C, and the time is 2h-4h; E. The heating rates of the first calcination and the second calcination are 2°C / min-5°C / min.
7. The method for preparing the transparent coating material for blocking infrared rays and ultraviolet rays according to claim 4, characterized in that: Before the zirconium-cesium-tungsten oxide micron-sized powder and the hollow sphere composite oxide micron-sized powder are mixed, the method further comprises: The zirconium-cesium-tungsten oxide micron-sized powder and the hollow sphere composite oxide micron-sized powder are respectively dispersed by ball milling in an alkaline solution and a second dispersant to obtain zirconium-cesium-tungsten oxide nano-sized powder and hollow sphere composite oxide nano-sized powder; The zirconium-cesium-tungsten oxide nano-powder, the hollow sphere composite oxide nano-powder and other raw materials are mixed to prepare a mixed slurry.
8. The method for preparing the transparent coating material for blocking infrared rays and ultraviolet rays according to claim 7, characterized in that: At least one of the following conditions is met: A. The pH of the alkaline solution is 7-10; B. The ball milling dispersion speed is 500rpm / min-3000rpm / min, and the time is 70h-74h.
9. A coating, characterized in that: The raw materials thereof include the transparent coating material for blocking infrared rays and ultraviolet rays as claimed in claim 3.
Citation Information
Patent Citations
Aqueous self-cleaning transparent heat-insulated nano-dope capable of fully shielding infrared ray and ultraviolet ray
CN102732108A
Infrared shielding microparticle, its manufacturing method, infrared shielding microparticle dispersion, infrared shielding element, and infrared shielding base material
JP2008291109A